Analysis of Instagram Ads on Consumer Behavior: Empirical Study of Villa Melayang in Bogor, Indonesia - Wulandari, Astri; Makarim, M. Dhafin (Manunggal Halim Jaya, 2026)
This study examines the influence of Instagram advertisements on consumer purchasing decisions related to Villa Melayang, an accommodation facility near Taman Safari Bogor. In the digital era, where social media platforms play a vital role in marketing strategies, understanding how Instagram content affects consumer behavior is crucial. The primary objective of this research is to analyze the relationship between Instagram promotions and consumer decisions to stay at the villa. A quantitative approach was employed by distributing questionnaires to 100 respondents, selected using Slovin's formula. Data analysis was conducted using statistical tools, including correlation tests. The results revealed a significant positive correlation (r = 0.735, p < 0.05) between Instagram advertising and purchasing decisions, indicating that engaging and interactive content can enhance consumer interest. Although Villa Melayang's Instagram posts are visually appealing, user engagement remains relatively low, suggesting a need to improve content interactivity. These findings underscore the importance of visually attractive social media strategies, encouraging user interaction to influence purchasing behavior. This research offers valuable insights for businesses, particularly in the hospitality industry, aiming to optimize their digital marketing efforts.